Influence of anthropometry on race performance in extreme endurance triathletes: World Challenge Deca Iron Triathlon 2006 - Knechtle, B.; Knechtle, P.; Andonie, J. L.; Kohler, G. (British Journal of Sports Medicine, 2007)
Objective: To investigate the influence of anthropometric variables on race performance in ultra-endurance triathletes in an ultra-triathlon.